2022
DOI: 10.1002/ppul.25971
|View full text |Cite
|
Sign up to set email alerts
|

Geoclimatic risk factors for childhood asthma hospitalization in southwest of Iran

Abstract: Background: Asthma is a chronic respiratory disease resulting from a complex interaction between genetic and environmental factors. Among environmental factors, climatic and geographical variations have an important role in increasing asthma hospitalization. The current study aimed to investigate the effect of geoclimatic factors on the occurrence of childhood asthma hospitalization in Fars province, southwest Iran. Method:We mapped the addresses of 211 hospitalized patients with childhood asthma (2016−2019) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…The authors found a significant correlation between urban residence and asthma hospitalization, however, did not find a significant correlation with climate variables such as mean annual evaporation, mean annual humidity, mean annual rainfall, or mean annual temperature. 8 These findings provide additional knowledge of the growing influence of climate change and social determinants of health on asthma care.…”
Section: Updates On Risk Factors For Asthmamentioning
confidence: 85%
“…The authors found a significant correlation between urban residence and asthma hospitalization, however, did not find a significant correlation with climate variables such as mean annual evaporation, mean annual humidity, mean annual rainfall, or mean annual temperature. 8 These findings provide additional knowledge of the growing influence of climate change and social determinants of health on asthma care.…”
Section: Updates On Risk Factors For Asthmamentioning
confidence: 85%
“…Similar to our results, Solé et al (2007) reported higher asthma prevalence among adolescents living in urban areas compared to the rural ones in Brazil. We previously found increased asthma hospitalization occurrences in urban regions of Fars province compared with rural areas (Kanannejad et al, 2022). The farming environment of rural areas is one explanation for lower asthma prevalence in such places (Strachan, 1989).…”
Section: Environmental Factorsmentioning
confidence: 90%
“…The slope was another significant environmental factor affecting acute asthma occurrence in Fars province, where more asthma hospitalization was detected in areas with a lower pitch. Our previous study on childhood populations showed the powerful effect of slope on asthma hospitalization (Kanannejad et al, 2022). It may be related to higher population density in regions with a downward slope that usually is connected with increased air pollutants, nanoparticles, and transmissible infectious viral agents (Bröms et al, 2009).…”
Section: Environmental Factorsmentioning
confidence: 97%
See 1 more Smart Citation
“…Asthma is characterized by airway obstruction, inflammation, and remodeling. The development of this disease is influenced by a complex interplay between genetic and environmental factors, along with the involvement of diverse immune and nonimmune cells 2–4 . Asthma inflammation involves the interaction and secretion of soluble mediators by various cell types, including immune cells (such as mast cells, eosinophils, and T cells) as well as structural cells (such as epithelial and endothelial cells, and fibroblasts).…”
Section: Introductionmentioning
confidence: 99%